“Actividades lúdicas en el proceso de enseñanza aprendizaje de la lectoescritura” - Pichucho Coyachamin, Luis Fernando (2022)
At present, one of the fundamental concerns focuses on play as an educational strategy, considering that it is one of the most complete activities that children carry out since childhood, thus promoting all areas of their development, in such a way that students they are empowered by learning. The teaching-learning process of literacy is a problem of a socio-academic nature that mainly affects children, from the first years of basic education, literacy, from a theoretical and scientific perspective is supported in different areas such as: social, educational and legal with a broad conceptual description of different authors and also with the support of electronic documents and information and communication technologies. For this reason, the objective of this research work is to determine how playful activities affect the development of the teaching-learning process of literacy in children in the fourth year of basic education at the Guaranda school belonging to the Pujilí Canton. The applied methodology transcended exploratory and descriptive research, while non-experimental research supported by bibliographic or documentary and field research was applied for the design, as well as observation techniques and the application of instruments such as the survey applied to students. and teachers helped verify and verify the results. In found results, teachers do not always use playful activities in the teaching-learning process, since they carry out repetitive and rote classes, therefore a more creative role of teacher is necessary for the development of motivating activities based on play and play for the student. Strengthening literacy in students.